Precursor lesions of uterine serous carcinoma – review of the literature - Sobczuk, Anna; Wrona, Marcin; Pertyński, Tomasz (Menopause Review/Przegląd Menopauzalny, 2007)
Uterine serous carcinoma (USC) is an uncommon but aggressive type of endometrial cancer associated with rapid progression of disease and a poor prognosis. The morphological and clinical features of the typical USC have been well delineated, but its precursor lesion is still under debate in terms of morphology as well as terminology. The putative precursor lesion of USC previously designated as endometrial intraepithelial carcinoma (EIC) or endometrial adenocarcinoma in situ or uterine surface carcinoma is now being referred to as serous EIC. Serous EIC is defined morphologically as replacement of endometrial surface epithelium and glands by frankly malignant cells that resemble the cells of the invasive high-grade endometrial carcinoma. Serous EIC is commonly associated with extrauterine serous carcinoma. Therefore it may be an early form of cancer rather than a precursor lesion. Endometrial glandular dysplasia (EmGD) is a newly defined entity that is commonly and specifically associated with serous EIC and USC. It has been proposed as a true precancerous lesion of USC based on recent studies showing morphological and molecular linkages between these 2 lesions.